Mesopredator control for waterfowl conservation : hunting reduces invasive raccoon dog abundance and predation on artificial nests - Selonen, Vesa; Deshpande, Purabi; Karhula, Kari; Lindén, Andreas; Toivola, Mikko; Laaksonen, Toni (Springer Nature, 2025)
The use of predator control as a conservation tool, for example to protect ground-nesting bird populations, remains a subject of ongoing debate. To justify the control or eradication of a predator, managers need to provide evidence on the success of the program. We evaluated the effectiveness of a raccoon dog control program (2021–2024) organized by governmental bodies around wetlands important for waterfowl conservation in Finland. The raccoon dog is an invasive species and a nest predator of waterfowl. We assessed control effectiveness by analysing how hunting methods and effort influenced catch and how varying hunting intensity across wetlands affected raccoon dog abundance measured with camera-traps. There was a moderate negative relationship between previous hunting efforts and monthly catch, indicating diminishing returns, but full eradication was not achieved. Among the four used hunting methods, hunting from dens proved the most efficient hunting method in relation to time used. The impact of catch on the subsequent number of camera-trap observations varied. Winter camera-trap data from feeding sites showed no decline in raccoon dog presence, potentially due to autumn immigration. However, hunting success showed a negative effect on raccoon dog camera-trap observations in spring (waterfowl breeding season), suggesting a substantial, but incomplete, raccoon dog population reduction. Consistent with this, raccoon dog predation of artificial nests decreased, without compensatory increases by other predator species, resulting overall in reduced nest predation. We conclude that control efforts reduce raccoon dog numbers and potentially benefit wetland bird species, but long-term success requires substantial and sustained effort.
Keywords: invasive species; nest predation; conservation; management; hunting; wetlands